2016
DOI: 10.1038/bjc.2015.462
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccination induces neutralising antibodies in oral mucosal fluids

Abstract: Background:Mucosal human papillomaviruses (HPV) are a major cause of cancers and papillomas of the anogenital and oropharyngeal tract. HPV-vaccination elicits neutralising antibodies in sera and cervicovaginal secretions and protects uninfected individuals from persistent anogenital infection and associated diseases caused by the vaccine-targeted HPV types. Whether immunisation can prevent oropharyngeal infection and diseases and whether neutralising antibodies represent the correlate of protection, is still u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 40 publications
1
37
0
2
Order By: Relevance
“…Recent studies showed no statistically significant correlations between IgG in sera and saliva against HPV‐6 and HPV‐18. In contrast, the levels of HPV‐16 IgG in sera and in oral fluids were statistically significantly correlated . Hanna et al .…”
Section: Hpv Diagnosismentioning
confidence: 89%
See 1 more Smart Citation
“…Recent studies showed no statistically significant correlations between IgG in sera and saliva against HPV‐6 and HPV‐18. In contrast, the levels of HPV‐16 IgG in sera and in oral fluids were statistically significantly correlated . Hanna et al .…”
Section: Hpv Diagnosismentioning
confidence: 89%
“…The current key question is whether the HPV vaccines also prevent HPV infections in the head and neck region. By now it is known that HPV vaccination induces HPV‐specific antibodies in saliva , including neutralizing antibodies . The concentrations of HPV‐16 and HPV‐18 antibody were approximately 3 logs lower in saliva than in serum after HPV vaccination .…”
Section: Prevention Of Hpv Infectionmentioning
confidence: 99%
“…In animal models, vaccination was found to provide protection against oral infections and lesions of canine oral papillomavirus [22]. Studies have shown that HPV vaccination-induced high titres of type-specific antibodies in oral fluids (which include the saliva secreted by the salivary glands and the oral mucosal transudate that originates from the capillaries though the gingival mucosa) [23,24]. Moreover, these antibodies are able to neutralise HPV-pseudovirions in vitro, as recently demonstrated by Handisruya et al [24].…”
Section: Primary Preventionmentioning
confidence: 80%
“…Studies have shown that HPV vaccination-induced high titres of type-specific antibodies in oral fluids (which include the saliva secreted by the salivary glands and the oral mucosal transudate that originates from the capillaries though the gingival mucosa) [23,24]. Moreover, these antibodies are able to neutralise HPV-pseudovirions in vitro, as recently demonstrated by Handisruya et al [24]. To date, only one study has evaluated the preventative potential of the HPV vaccine against oral HPV infections.…”
Section: Primary Preventionmentioning
confidence: 95%
“…One development that may help in this effort is the recent Food and Drug Administration approval of the two‐dose HPV vaccine (Petrosky et al., ; https://www.cdc.gov/mmwr/volumes/65/wr/mm6549a5.htm), which in theory would result in fewer office visits and more people being vaccinated because of reduced cost and improved efficiency of vaccine dose completion. Another development that may prove important is the recent finding that HPV vaccines induce neutralizing antibodies in oral fluids (Handisurya, Schellenbacher, Haitel, Senger, & Kirnbauer, ), which is suggestive that such vaccines could prevent infections in the oral mucosa and possibly oropharyngeal cancer later in life.…”
mentioning
confidence: 99%